Acute pain and self-directed discharge among hospitalized patients with opioid-related diagnoses: a cohort study - Peggy Compton; Shoshana V. Aronowitz; Heather Klusaritz; Evan Anderson (BMC, 2021)
Abstract Background Patients with substance use disorders are more likely than those without to have a self-directed hospital discharge, putting them at risk for poor health outcomes including progressing illness, readmissions, and death. Inadequate pain management has been identified as a potential motivator of self-directed discharge in this patient population. The objective of this study was to describe the association between acute pain and self-directed discharges among persons with opioid-related conditions; the presence of chronic pain in self-directed discharges was likewise considered. Methods We employed a large database of all hospitalizations at acute care hospitals during 2017 in the city of Philadelphia to identify adults with opioid-related conditions and compare the characteristics of admissions ending with routine discharge versus those ending in self-directed discharge. We examined all adult discharges with an ICD-10 diagnoses related to opioid use or poisoning and inspected the diagnostic data to systematically identify acute pain for the listed primary diagnosis and explore patterning in chronic pain diagnoses with respect to discharge outcomes. Results Sixteen percent of the 7972 admissions involving opioid-related conditions culminated in self-directed discharge, which was more than five times higher than in the general population. Self-directed discharge rates were positively associated with polysubstance use, nicotine dependence, depression, and homelessness. Among the 955 patients with at least one self-directed discharge, 15.4% had up to 16 additional self-directed discharges during the 12-month observation period. Those admitted with an acutely painful diagnosis were almost twice as likely to complete a self-directed discharge, and for patients with multiple admissions, rates of acutely painful diagnoses increased with each admission coinciding with a cascading pattern of worsening infectious morbidity over time. Chronic pain diagnoses were inconsistent for those patients with multiple admissions, appearing, for the same patient, in one admission but not others; those with inconsistent documentation of chronic pain were substantially more likely to self-discharge. Conclusions These findings underscore the importance of pain care in disrupting a process of self-directed discharge, intensifying harm, and preventable financial cost and suffering. Each admission represents a potential opportunity to provide harm reduction and treatment interventions addressing both substance use and pain.